TALAK DI LUAR PENGADILAN DALAM PANDANGAN MUHAMMADIYAH - Safana Fauziyah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The cause of marriage breakdown is divorce. Divorce in Islam has many varieties, including talak, khuluk, li'an, fasakh. Divorce in divorce legislation is divided into two, namely talak divorce and contested divorce. In Islamic law, divorce is primarily the husband's absolute right, so it does not require witnesses or recording, the husband can give divorce to his wife anytime and anywhere. The results of this research indicate that the Tarjih and Tajdid Councils. The central leadership of Muhammadiyah is of the view that divorces carried out outside of court are invalid because this view is in accordance with the law in force in Indonesia.